The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1103/physreve.92.023010
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of the turbulent dynamo

Abstract: The origin of strong magnetic fields in the Universe can be explained by amplifying weak seed fields via turbulent motions on small spatial scales and subsequently transporting the magnetic energy to larger scales. This process is known as the turbulent dynamo and depends on the properties of turbulence, i.e. on the hydrodynamical Reynolds number and the compressibility of the gas, and on the magnetic diffusivity. While we know the growth rate of the magnetic energy in the linear regime, the saturation level, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 59 publications
(148 reference statements)
13
120
1
1
Order By: Relevance
“…In this section we presented a quantitative comparison of the turbulent dynamo in the analytical and semi-analytical Kazantsev models by Subramanian (1999), Schober et al (2012cSchober et al ( ,a, 2015 and Bovino et al (2013) with 3-D simulations of supersonic MHD turbulence. We found that the dynamo operates at low and high magnetic Prandtl numbers, but is significantly more efficient for Pm > 1 than for Pm < 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we presented a quantitative comparison of the turbulent dynamo in the analytical and semi-analytical Kazantsev models by Subramanian (1999), Schober et al (2012cSchober et al ( ,a, 2015 and Bovino et al (2013) with 3-D simulations of supersonic MHD turbulence. We found that the dynamo operates at low and high magnetic Prandtl numbers, but is significantly more efficient for Pm > 1 than for Pm < 1.…”
Section: Discussionmentioning
confidence: 99%
“…It increases with Pm similar to the growth rate and is also well converged with increasing numerical resolution. For Pm 10, (E m /E k ) sat seems to become independent of Pm (and thus independent of Rm, because we have constant Schober et al (2015) are shown in the low-Pm and high-Pm limits -as for the growth rate, ϑ = 0.45 is the most relevant case for this comparison. The analytic prediction agrees qualitatively with the results of the MHD simulations, but similar to the limitations of the theories for the growth rate, more work is needed to incorporate the mode mixture (solenoidal versus compressive) in the saturation models.…”
Section: Dependence On Magnetic Prandtl Numbermentioning
confidence: 99%
“…As pointed out by Murphy (2009), a potential difficulty is however the increasing strength of the cosmic microwave background at high redshift, enhancing the inverse Compton emission and providing an additional loss mechanism for the cosmic ray electrons. It is thus conceivable that the latter may lead to a modification or a breakdown of the correlation at very high redshift due to differences in the energy loss mechanisms of cosmic rays Schleicher & Beck 2013;Schober et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…And the system was forced magnetically (Park and Blackman 2012b) with f k = 0.02 with the resolution of 288 3 . We have a magnetic Prandtl number of Pr M =ν/η = 750, which we take as a good approximation for the large values Pr M ≫ 1 expected in the early universe (Kulsrud 1999, Schekochihin et al 2002, Schober et al 2012, and references there in). Turning on and off the forcing function (0 < t < 1, simulation time unit), we imitate an ephemeral event which had driven a celestial (MHD) system in the past.…”
Section: Simulation and Methodsmentioning
confidence: 96%
“…Also Haugen et al (2004) reported a critical Re M, crit in the range between ∼35 and ∼70. On the other hand, Schober et al (2012) proposed values of Re M, crit ∼ 110 for incompressible gas and Re M, crit ∼ 2700 for extremely compressible gas, i.e., for Kolmogorov and Burger turbulence, respectively. Going further, Federrath et al (2011), Schober et al (2012), and Schleicher et al (2013) explored the influence of Mach number and Pr M on the amplification of magnetic field in the small scale regime for the formation of primeval stars.…”
Section: Introductionmentioning
confidence: 98%